Urgensi Integrasi Zona Integritas dan Pelayanan Publik - Mukti Mukti; Muhammad Win Afgani; Afriantoni Afriantoni (Journal on Education, 2024)
This research aims to examine and analyze the urgency of the integration of integrity zones and public services in Indonesia. This type of research uses normative legal research methods. The approach to this research is carried out with a legislative approach combined with a conceptual approach. The result of this research is that the regulation of integrity zones in Indonesia has undergone several changes, because with the development of this integrity zone, not only as a prevention and eradication of corruption but also public services which initially had many overlapping processes, the quality of human resources that was relatively low, the occurrence of abuse of authority, and supervision that is not optimal is better. The integrity zone is an obligation, not just an option. This will be an integrity zone as a success in the bureaucratic reform program in Indonesia, especially in the physical public service sector.